Pré-natal coletivo: uma análise crítica a partir da percepção das mulheres na estratégia saúde da família em João Pessoa-PB - Fernandes, Edjane Pessoa Ribeiro (2020)
Introduction: In order to favor woman's autonomy in front of challenges that motherhood imposes, initiatives aimed at humanized assistance since pregnancy have been implemented. In this context, collective prenatal care is configured as a strategy to promote and strengthen women's sexual and reproductive rights, which favors the collaborative model of health care, involving professionals from different categories. Objective: Analyze the collective prenatal from perspective of women from a Family Health Unit in João Pessoa-PB. Methodology: This is a qualitative study carried out from the approach of action research, and from participant observation. Data collection occurred between January and April/2019. The use of the semi-structured interview technique and had the participation of ten pregnant women involved in collective prenatal care. For the treatment of empirical material, the method of content analysis was used in the conception of Bardin, from the perspective of thematic analysis. Results: After analyzing the data, three categories were highlighted: Collective prenatal care as a space for health promotion; shared knowledge; collective prenatal care: strengths and weaknesses. Collective prenatal care was evidenced as a space for self-care, strengthening the maternity support network, women’s self-confidence regarding their choices throughout the pregnancy-puerperal period, building new friendships, learning relevant themes in shared experiences and the integration of actions involving different professionals. However, the necessity for a large and comfortable enviroment, the discomfort of some pregnant women in the collective consultation and some challenges to be overcome. Conclusion: Collective prenatal care is configured as a strategy that, based on the involvement of professionals in several categories, with subsidies in the dialogue to build bonds between the participants, as well as between the pregnant-professional-service, making this active subject of their care process. This approach seeks the practice of comprehensive care for pregnant women and makes it possible to rethink work processes in Primary Health Care, especially in the FHS, the first level of the SUS Health Care Network.